Comportamento de estruturas reforçadas com geossintéticos sob acções sísmicas - Castorina Silva Vieira (2005)
This paper presents a brief description of the behaviour of geosynthetic-reinforced structures during some earthquakes occurred in the Nineties, namely Northridge (United States), Hyogoken-Nambu or Kobe (Japan) and Chi-Chi (Taiwan). It is also presented a comparative study between an embankment and a geogrid-reinforced embankment subjected to a seismic action for the greater seismicity area of continental Portugal.